Adopting an Open Innovation Program with Supply Chain Management in China: A Case Study. Issue 1 (2nd January 2018) - Lau, Antonio K. W.; Lee, Leo W. Y.; Lai, Kee-Hung; Lee, Peter K. C.
Abstract: This study examines how an open innovation program can be implemented in practice by a foreign company operating in China with due consideration of traditional supply chain management practices. A case study of an open innovation initiative in a renowned global electrical appliance company in China is explored. The study has found that supply chain managers can play an important role in innovation sourcing, provided an open innovation perspective is adopted. In addition, an open innovation framework complemented by an open innovation funnel is presented. The framework provides new practical insights for engineering managers seeking to implement open innovation programs. The study bridges the gap between academic studies and industrial practice regarding the roles of different functional units in an environment of open innovation.